2021
DOI: 10.1007/s11845-021-02784-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrauma admissions and COVID-19: a National Centre experience

Abstract: Background To investigate the impact of COVID-19 on trauma admissions to a National Neurosurgical Centre in Ireland. Methods Retrospective analysis of a prospectively maintained database of all trauma admissions to the National Neurosurgical Centre at Beaumont Hospital, Dublin, during the period March 1 to May 31, 2019 and 2020. Primary outcome was 30-day mortality rate. Secondary outcomes included time transfer time, time from admission to time of surgery, and intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, we believe that our findings are robust and reflect a true improvement in TBI care, as we alone report a reduction in LOS while others saw both an increase in head injury severity and an increase in LOS during the pandemic. 12,13 Furthermore, the QIP was paused during staff redeployment.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that our findings are robust and reflect a true improvement in TBI care, as we alone report a reduction in LOS while others saw both an increase in head injury severity and an increase in LOS during the pandemic. 12,13 Furthermore, the QIP was paused during staff redeployment.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in daily life were also visible in the epidemiology of TBI. Retrograde analysis from single-centers in Austria [ 19 ], Italy [ 20 ], France [ 21 ], Finland [ 22 ], the Netherlands [ 23 ], Ireland [ 24 ], and a multi-center study from Austria, the Czech Republic, and Switzerland [ 25 ], as well as studies around the world [ 26 , 27 ], demonstrated a decreased number of TBI cases in comparison with previous years and months preceding the pandemic. In addition, the mechanism of the injuries, patterns, severity, and outcomes were also influenced by the SARS-CoV-2 pandemic.…”
Section: Introductionmentioning
confidence: 99%